Parathyroid function and cardiovascular remodeling in arterial hypertension patients - B. G. Iskenderov; L. F. Burmistrova; T. V. Lokhina; G. N. Abramova; N. A. Timofeeva; T. M. Shibaeva (Кардиоваскулярная терапия и профилактика)
Aim. To investigate structure and function of left ventriculum (LV) and brachial artery (BA) in arterial hypertension (AH) patients, according to blood levels of parathyroid hormone (PTH).Material and methods. In total, 95 untreated patients with Stage I-III AH were examined. Blood PTH, total calcium levels, and 24-hour urine calcium excretion were measured. All participants underwent Doppler echocardiography, 24-hour blood pressure monitoring (BPM), and BA ultrasound. According to PTH levels, the patients were divided into three groups: Group I – 0-25 pg/ml, Group II – 26-50 pg/ml, and Group III – 51 pg/ml.Results. LV hypertrophy prevalence in Group III was 80,6%, in Group I – 43,7%. In “dippers” (24-hour BPM data), PTH level and 24-hour urine calcium excretion were 1,5 times lower than in “non-dippers”. Comparing to Group I, Group III demonstrated significantly greater intima-media thickness (+17,8%) and linear blood flowvelocity (+19,7%), but lower BA diameter (417,3%) and endothelium-dependent vasodilatation (415,5%).Conclusion. PTH levels correlated with prevalence and severity of LV and BA remodeling.